UM SALVE A TODAS AS COMUNIDADES:REPRESENTAÇÕES SOCIAIS SOBRE VIOLÊNCIA DE RAPPERS QUE FREQUENTAM O CREAS II DE LONDRINA-PR - Rosas, Rudy Heitor (2017)
The following dissertation is the result of an approximation between rap and violence. The initial spark of the research process was Cultural Criminology which, presenting several researches on rock and violence, showed that would be possible a similar research, but with a more national style. Rap was selected because it is currently the music of a stigmatized part of the population, just as the rockers were. To approach the social, it was defined that the research would ally theoretical knowledge on the central themes (rap and violence), with empirical research, to really approach reality and theory. After some incursions into the research, it was defined that the object of this work would be the social representations of rappers about violence. The selected field was CREAS II of Londrina - Paraná. The venue was chosen for sheltering rap composers who are in a situation of violence, either through committing or through living in areas considered violent. The methodology that guides the whole process is the Case Study, with qualitative approach to the research problem. Participant observation, semi-structured interview and documentary research were selected as collection techniques and Bardin content analysis as a technique for the analysis of collected data. The field research was from April to August of 2016, in addition to other virtual contacts. To support the analysis, some theoretical references were chosen: Norbert Elias, with the concepts of mimesis, sociodynamics of power and relationship between established and outsiders; Serge Moscovici with the Social Representations, thus facilitating a better use of what is shared in the common sense of the rappers; And Slavoj Zizek with his categories of violence. The research made it possible to perceive the violence through the reports and experiences of five interviewed subjects, both in their speeches and in their compositions, which often give vent to subjects that they cannot share in daily life.